How Jii Companies' Cash and Quick Ratios to Profitability: Penelitian - Rina Malahayati; Tri Pertiwi; Muridha Hasan; Riska Aramita (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2026)
This research was designed to investigate the empirical conditions and evaluate the impact exerted by the Cash Ratio (CR) and Quick Ratio (QR) on corporate profitability (represented by Return on Assets/ROA) among constituents of the Jakarta Islamic Index (JII) from 2023 to 2025. Adopting a quantitative framework alongside descriptive and verification methods, this investigation selected 30 prominent sharia-compliant corporations as the analysis sample. Hypothesis testing was executed through quadratic non-linear regression models operated via SPSS version 24. Descriptive analysis identified three unique interaction typologies: a negative trend stemming from unutilized funds, a positive trajectory generated by proportional liquidity, and an aggressive working capital loop driven by minimal cash holdings. Based on partial assessment (t-test), the linear dimension of the Cash Ratio significantly and positively stimulates ROA (t-value = 2.250); Sig. = 0.027 < 0.05). Conversely, its quadratic element (CR2) yields a negative coefficient (-1.914), signaling an inverted U-shaped non-linear tendency, albeit statistically non-significant Sig. = 0.131 > 0.05). Meanwhile, neither the linear nor quadratic expressions of the Quick Ratio demonstrate a meaningful impact on ROA variations. Jointly (F-test), the combined model significantly accounts for corporate ROA shifts (F-value} = 4.02); Sig. = 0.005 < 0.05), offering an R-squared value (R2) of 15.9%, with the dominant 84.1% explained by variables omitted from this model. These findings imply that corporate treasurers within JII should establish a calculated cash threshold to suppress the opportunity cost linked to stagnant cash pools.